Assessment of the coronal root canal morphology of permanent maxillary first molars using digital 3D-reconstruction technology based on micro-computed tomography data - Mudan Wang; Yuxuan Gao; Qi Deng; Yuan Gao; Dongzhe Song; Dingming Huang (Elsevier, 2023)
Background: The design of minimally invasive access has become a hotspot. This study aimed to evaluate the coronal root canal morphology of permanent maxillary first molars to facilitate the design of endodontic access cavities for minimally invasive linear access. Materials and methods: A selection of 91 permanent maxillary first molars was evaluated. Three-dimensional tooth models were reconstructed using micro-computed tomography data. Root canal prevalence and coronal root canal landmarks were recorded. The positional coordinates of landmarks in the horizontal plane and the angles and directions of coronal root canal curvature in the horizontal and axial planes were also assessed. Results: The detection rates of the mesiobuccal (MB), distobuccal (DB), and palatal (P) canals were 100%, whereas that of the second mesiobuccal (MB2) canals was 68.1%. All landmarks were located near the central fossa. In the axial plane, the average angles of coronal root canal curvature were DB (27.05°) > MB (25.43°) > P (20.71°) in teeth with three canals, and MB2 (33.20°) > MB (29.61°) > DB (28.40°) > P (23.69°) in teeth with four canals. In the horizontal plane, the average angles were P (78.15°) > DB (42.34°) > MB (32.41°) in teeth with three canals, and P (81.26°) > DB (43.44°) > MB (41.22°) > MB2 (9.41°) in teeth with four canals. Conclusion: In maxillary first molars, coronal root canals tend to converge towards the occlusal surface. The results of this study could be applied to improve the precision of endodontic access cavity designs of minimally invasive access.